Nautilids from the upper cretaceous of the James Ross Basin, Antarctic Peninsula - Cichowolski, Marcela; Ambrosio, Alfredo; Concheyro, Graciela (Antarctic Science)
To date, Cretaceous nautilids from the Antarctic Peninsula have received little attention and only a single species had been reported, Eutrephoceras simile Spath, from Seymour, Snow Hill, and James Ross islands. Currently, it is considered a synonym of Eutrephoceras subplicatum (Steinmann), which has also been described from the Upper Cretaceous of central Chile, southern Argentina and Angola. Here, we report and describe E. subplicatum in detail, based on specimens from the Lower Campanian–Maastrichtian of Vega, Seymour and James Ross islands, presenting, for the first time, embryonic conch features related to the palaeoecology of these organisms. The nauta of this species had a diameter of approximately 30 mm with 5–6 septa. In addition, we describe a new species, Eutrephoceras antarcticum, and one specimen assigned to the same genus in open nomenclature, both recovered from the Lower Campanian beds of James Ross Island. Fil: Cichowolski, Marcela. Universidad de Buenos Aires; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ambrosio, Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina. Universidad de Buenos Aires; Argentina Fil: Concheyro, Graciela. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad de Buenos Aires; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina